Analysis of environmental factors impact on water transparency off southeastern Vietnam - Sun, Yan; Xu, Yuanxing; Liu, Dazhao; Xu, Guangjun (Frontiers in Marine Science, 2023)
Seawater transparency, one of the important parameters to evaluate the marine ecological environment and functions, can be measured using the Secchi disk depth (SDD). In this study, we use multi-source remote sensing data and other fused data from 2011 to 2020 to study the spatial distribution and variation of SDD off southeastern Vietnam. The monthly average of SDD in the study area has obvious seasonal variation characteristics and shows a double peak characteristic. An important observation is a significant decrease in transparency from July to September each year, which is far lower than other nearby seas. To study this low SDD phenomenon, the generalized additive model (GAM) is used to determine the main environmental factors. The response relationship between SDD and environmental factors on different time scales is explained through empirical mode decomposition (EMD) analysis experiments. The results show that the comprehensive explanation rate of the GAM model is 72.1%, and the main environmental factors affecting SDD all have non-linear response relationships with SDD. The contributions are ranked as sea surface salinity (SSS)> offshore current velocity (Cu)> wind direction (WD)> offshore Ekman transport (ETu)> sea surface temperature (SST)> mean direction of wind waves (MDWW). SDD is positively correlated with SSS and SST, and negatively correlated with Cu and ETu. SSS, Cu, ETu, and SST have a significant effect on SDD at interannual scales. Long-term changes in SDD are driven by SSS, Cu, WD, and SST. Generally, SSS has the most comprehensive impact on SDD. WD indirectly has a non-negligible impact on SDD by changing ocean dynamics processes.